186 Reduced pericyte insulin signalling causes abnormal developmental angiogenesis. (5th June 2017) - Warmke, Nele; Griffin, Kathryn J; I Slater, Charles; MN Walker, Andrew; Yuldasheva, Nadira Y; Cubbon, Richard M
Abstract : Introduction: Microvascular endothelial cells (ECs) are surrounded and supported by mural cells called pericytes. Via paracrine signalling and gap junctions, pericytes interact with ECs, modulating angiogenesis and vessel homeostasis. Diabetes-associated vascular complications are characterised by vascular leakage and dysfunctional neovascularization, both associated with pericyte loss in various vascular beds, including the retina. Pericytes are particularly sensitive to a hyperglycaemic environment, which results in their apoptosis and subsequent changes in vascular health. Insulin also has important effects on pericyte biology in vitro, yet the significance of this in vivo and in regard to diabetes remains unexplored. Methods: Using a mouse model with a pericyte specific knockout of the insulin receptor (PIR-/-), created by crossing PDGFRβ²-Cre mice with insulin receptor – floxed – mice, we investigated the role of pericyte insulin signalling in developmental retinal angiogenesis in vivo and on pericyte function in vitro . Results: At postnatal day 5, PIR-/- retinas show hyper-vascularized venous regions with an increase in venous vascular density (57.6±1.0% compared to 52.1±0.6% in littermate controls, p=0.0003) along with an increase in sprouting tip cell formation at the vascular front (1.7±0.05 versus 1.5±0.06 per 100µm in controls, p=0.006). Pericyte coverage at postnatal day 5 appears comparable in PIR-/- and control, but pericyte abundance is strikingly reduced by 20% in the mature adult retinal vasculature (0.8±0.03 and 1.0±0.05 per 100µm in controls, p=0.002). However, the differential vascularity of neonatal retinas did not persist in adulthood (18.1±0.7 mm versus 18.3±0.5 mm per mm 2 region of interest in control). Basic metabolic phenotyping of adult mice shows no difference in body weight or fasting blood glucose levels (5.0±0.2 mmol/L and 4.7±0.2 mmol/L in PIR-/- and control mice, respectively), but interestingly, preliminary assessment of pericyte function in vitro suggests enhanced proliferation of PIR-/- pericytes. Conclusions: Pericyte-specific insulin receptor knockout affects developmental retinal angiogenesis in vivo . Sprouting and remodelling of the retinal vasculature are altered, associated with a reduction in pericyte coverage in adulthood, recapitulating some characteristics of proliferative diabetic retinopathy. The underlying molecular mechanism remains unclear, but these results indicate that adequate pericyte insulin signalling is important for pericyte function, and hence vascular stability.